Financial Development and Economic Growth in Iraq: The Role of Financial Institutions using NARDL - Gailan Ismael Abdullah; Raddam Saab Abbas (Scholar Express Journals, 2022)
In this research, we examine the relationship between financial development through indicators of financial institutions and economic growth in Iraq by annual data (2004–2019). Unlike the studies and as an alternative to the conventional method in using the ARDL model, the Nonlinear Autoregressive Distributed Lag (NARDL) model and Toda-Yamamoto causality were applied to analyze the relationship between financial development and economic growth. The results of the F-bounds test show that there is a stable long-run relationship between indicators of financial institutions (financial depth, financial efficiency, financial access) and economic growth. On the other hand, the results of the causality test, show that there is no causal relationship between all the indicators of financial institutions and economic growth. The dynamic impact multiplier shows that (a) the final impact of financial depth of financial institutions was negative, that is, economic growth declines due to a decrease in the level of financial depth of financial institutions; (b) the final impact of the financial efficiency of financial institutions at the beginning of the period is positive and then stabilizes at the negative level, that is, economic growth declines due to a decrease in the efficiency of financial institutions; and (c) the final impact of financial access to financial institutions was positive, that is, economic growth increases due to the high level of financial access to financial institutions
Keywords: Financial Development; Economic Growth; Nonlinear impact; dynamic multiplier